Angiodysplasia of Right Colon.: Angiographic and Anatomopathological Diagnosis - Tiscornia, Eduardo; Sálice, Mario; Pizarrosa, Carlos; Vercelli, Jorge; Carriquiry, Luis; Harretche, Martín; Mañana, Graciela; Cotelo, Ana; Oheninger, Carlos (Cirugía del Uruguay, 1981)
Angiodysplasia of colon has been reported as a frequent disease and cause of unexplained gastrointestinal bleeding. The authors have attemped to present angiographic and anatomopathologic diagnostic elements, as illustrated by 2 cases. Diagnosis is made almost exclusively through mesenteric arteriography and its anatomopathologic confirmation demands not only a specialized technique but, above al1, coordination between Surgeon, Radiologist and Anatomopathologist, for correct handling of the anatomic specimen.